Metadata and Semantics Research 6th Research Conference, MTSR 2012, Cádiz, Spain, November 28-30, 2012. Proceedings - Dodero, Juan Manuel.; Dodero, Juan Manuel.; Palomo-Duarte, Manuel.; Palomo-Duarte, Manuel.; Karampiperis, Pythagoras.; Karampiperis, Pythagoras. (Communications in Computer and Information Science,, 2012)
This book constitutes the refereed proceedings of the 6th Metadata and Semantics Research Conference, MTSR 2012, held in Cádiz, Spain, in November 2012. The 33 revised papers presented were carefully reviewed and selected from 85 submissions. The papers are organized in a general, main track and several others: a track on metadata and semantics for open access repositories, research information systems and infrastructures, a second on metadata and semantics for cultural collections and applications, and finally one on metadata and semantics for agriculture, food and environment.